Process-structure-properties of additively manufactured continuous carbon fiber reinforced thermoplastic composite - Goh, Guo Dong (Nanyang Technological University, 2020)
Fiber-reinforced polymer (FRP) composites have been widely used in various applications such as aircraft structures due to their high strength-to-weight ratios and excellent corrosion resistance. The fused filament fabrication (FFF) has become one of the well-received additive manufacturing (AM) techniques to fabricate FRP composites due to its ability to align continuous fibers at tow level. It takes advantage of the fibers’ directional strength to distribute loads throughout a structure and allows more design flexibility for novel composite structures to be developed. The extrusion of continuous FRP composites presents a new research topic on the improvement of interlaminar properties of FRP composites. This research investigates the extrusion process of continuous FRP composites and the mode I interlaminar fracture toughness (ILFT) of FRP composites, which dictates the delamination resistance of composites. In this thesis, the prior arts of using various AM techniques to fabricate discontinuous and continuous FRP composites are analyzed. The anisotropic thermal behavior of the AM continuous carbon fiber-reinforced thermoplastic (CFRTP) renders more in-depth investigation into the temperature history of the AM CFRTP. A numerical heat transfer model is developed to study the temperature profile of the extruded composite filament in the extrusion process. The model will advance the field of extrusion of continuous FRP composites by allowing the prediction of the process parameters for the development of new continuous FRP composite filament. In the process-structure-property study, the formation of groove, the flatness of the top surface, the waviness of extruded composite filament, and the shearing of matrix from the fiber surface are among the factors that are found to have contributed to porosity of the printed composite parts which have direct impact on the mode I ILFT. The occurrences of these phenomena are very much related to the rheological properties of the AM CFRTP. Process parameters such as print speed, nozzle and bed temperatures would be able to control the porosity by changing the viscosity and shear rate. Nonetheless, interdiffusion of polymer chains at the interlayer boundary is found to be playing the major role in providing the mode I ILFT. It is found that the highest attainable mode I ILFT is 943 J/m2 and is achieved by using low print speed (7 mm/s), high nozzle temperature (265 oC), and high bed temperature (70 oC). Mechanical properties and the failure modes of AM CFRTP are evaluated. The anisotropic nature of the AM CFRTP is apparent in the tensile, compression, and shear modes, which is attributed to the nature of the carbon fibers. It is found that z-direction tensile strength (5.3 MPa) is lower compared to x- (808 MPa) and y- directions (39 MPa). The huge difference in mechanical properties in two transverse directions (y and z directions) was likely due to the difference in the effective contact surface of the intralayer and inter layer boundaries as evidenced in the fracture analysis. Lastly, the ability of the extrusion process to fabricate a geometrically complex structure is demonstrated by printing a quadcopter structure. These findings contributed to the scientific knowledge on how printing parameters would affect the mode I ILFT through systematic investigation of material science of the AM CFRTP and heat transfer of the extrusion process.